2021
DOI: 10.1371/journal.pone.0243691
|View full text |Cite|
|
Sign up to set email alerts
|

Bacteriological and histopathological findings in cetaceans that stranded in the Philippines from 2017 to 2018

Abstract: The relatively high frequency of marine mammal stranding events in the Philippines provide many research opportunities. A select set of stranders (n = 21) from 2017 to 2018 were sampled for bacteriology and histopathology. Pertinent tissues and bacteria were collected from individuals representing eight cetacean species (i.e. Feresa attenuata, Kogia breviceps, Globicephala macrorhynchus, Grampus griseus, Lagenodelphis hosei, Peponocephala electra, Stenella attenuata and Stenella longirostris) and were subjecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In the first period, the fecal microbiota was dominated by the Shigella , Streptococcus , Enterococcus , Lactobacillus, and Escherichia genera. Shigella and Escherichia have been found to co-occur in the feces of captive belugas and Pacific white-sided dolphins ( 42 ), dwarf sperm whale ( Kogia breviceps ) ( 43 ), and harbor seals ( 44 ). However, it is often considered as a disease-causative agent for humans and other primates, but it remains unclear if it is pathogenic to other mammals, including marine ones.…”
Section: Discussionmentioning
confidence: 99%
“…In the first period, the fecal microbiota was dominated by the Shigella , Streptococcus , Enterococcus , Lactobacillus, and Escherichia genera. Shigella and Escherichia have been found to co-occur in the feces of captive belugas and Pacific white-sided dolphins ( 42 ), dwarf sperm whale ( Kogia breviceps ) ( 43 ), and harbor seals ( 44 ). However, it is often considered as a disease-causative agent for humans and other primates, but it remains unclear if it is pathogenic to other mammals, including marine ones.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, in veterinary medicine, E. fergusonii has been reported to cause enteritis, and septicemia in horse and goat, fibrinonecrotic typhlitis in fowl, and fibrinous bronchopneumonia in cattle ( 18 ). Although a case report reported isolation of E. fergusonii in lungs of Globicephala macrorhynchus ( 19 ), its pathology and clinical importance have rarely been reported in aquatic organisms; therefore, it is not considered as the primary causative agent of sepsis in aquatic organisms, including dolphins. Prompt diagnosis and adequate clinical treatment are pivotal for the prognosis of sepsis in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt diagnosis and adequate clinical treatment are pivotal for the prognosis of sepsis in neonates. Antimicrobial resistance (AMR) was reported in E. fergusonii ( 19 21 ). Previous studies reported its wide-ranging resistance against nitrofurantoin, ciprofloxacin, ceftriaxone, amikacin, oxytetracycline, tetracycline, amoxicillin, amoxicillin-clavulanic acid, ampicillin, cefoxitin, penicillin, nalidixic acid, quinolone, and erythromycin ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations